A literature review of interventions to reduce stress in doctors. (January 2020) - Locke, Rachel; Lees, Amanda
Aim: Stress is prevalent among doctors, and interventions are offered, often as part of their continuing professional development, to help doctors learn in the workplace about the recognition, prevention and management of the harmful effects of stress. The aim of this review was to examine existing research to ascertain the features of successful educational interventions with practising doctors and any factors that may affect outcomes. Methods: We searched key databases for papers published between 1990 and 2017 on the themes of stress that included an education-based intervention and practising doctors. Using an inclusive approach to the review, a broad evaluation was made of the primary research using both quantitative and/or qualitative evidence where the study reported a positive outcome in terms of stress management. Results: Review criteria were met in 31 studies of 1, 356 originally retrieved. Three broad categories of interventions emerged from the coding process: mindfulness-type ( n = 12), coping and solutions focused (CSF) ( n = 12) and reflective groups ( n = 7). There is evidence that these interventions can be successful to help doctors deal with stress. Based on the results from this review, an original guide is advanced to help educators choose an educational intervention. Conclusion: Although evidence for some interventions may be 'hierarchically stronger', it is misleading to assume that interventions can be imported as successfully into any context. Factors such as medical specialty and health care systems may affect which intervention can be used. The guide offers an evidence base on which further research can be built.